Wireless EMG Monitoring System for Biceps Muscle Recovery - Kamalruzaman, Nurul Izwani; Abdul Jamil, Muhammad Mahadi (Evolution in Electrical and Electronic Engineering, 2025)
Muscle recovery is an essential process in the treatment of patient with muscle injuries, especially the biceps muscle. However, current monitoring methods are still not very accurate or reable in tracking patient progress during rehab sessions, this make it hard to know if the treatment is working and can lower the patient’s motivation. Additionally, patient who live far away often have trouble going to rehab session regularly. This can cause low attendance and slower recovery. This project aims to create a wireless EMG monitoring system to track biceps muscle activity in real time more effectively. The main system uses an ESP32, EMG sensor and OLED display and the Blynk IoT platform for monitoring. The result show that the system can accurately record biceps muscle activity with peak EMG readings reaching 4095 bit and 100% signal detection accuracy